Enhanced absorption in periodic one-dimensional metallic-organic periodic structure - Thapa K.B.; Mishra N.K.; Pandey G.N.; Jagmandar; Ojha S.P. (My University, 2025)
We show theoretically that the absorption of one dimensional metal-organic periodic structure (1D MOPS) can be enhanced due to organic constituents. We have used simple transfer matrix method to calculate the absorption, transmittance and reflectance of the 1D MOPS systems. The absorption, transmittance and reflectance of 1D MOPS containing 3.5 periodic of Ag/N,N′-bis-(1- naphthyl)-N,N′diphenyl-1,1biphenyl-4,4diamine (NPB) structure are calculated taking optical constant of NPB [1] and Ag [2]. The enhanced absorption of the considered structure is obtained in the visible and near infrared regions. Besides this, we have also studied the absorption, transmittance and reflectance of the 1D MOPS with air and glass substrates. We find that the absorption is enhanced with variation of thickness of organic layer (NPB). Such absorption enhancement in 1D MOPS could allow many potential applications in photothermal technology, thermo photo-voltaic and blackbody emission.